A fast algorithm for solving diagonally dominant symmetric quasi-pentadiagonal Toeplitz linear systems - Belhaj, Skander (2021)
In this paper, we develop a new algorithm for solving diagonally dominant symmetric quasi-pentadiagonal Toeplitz linear systems. Numerical experiments are given in order to illustrate the validity and efficiency of our algorithm.